Knowledge on practice of weaning among the mothers with infant below six months of age in Salem, Tamilnadu - Dhanasekaran, N (Journal of College of Medical Sciences-Nepal, 2015)
Background & Objectives: Weaning is essential to child nutrition, which reduce infant mortality rate and related malnutrition with healthy feeding practice. Hence the mothers are expected to be knowledgeable on weaning. Objectives: To assess the knowledge on practice of weaning, to compare the knowledge on practice and to find out association between the knowledge scores of mothers with infant below 6 months with selected demographic variables. Materials and Methods: A descriptive design with cross sectional survey approach was undertaken to assess the knowledge on practice of weaning mothers with infant below 6 months of age in selected hospital, Salem, Tamil Nadu. Fifty mothers were selected by purposive sampling technique and data was collected by using structured interview schedule from 06/11/14 to 20/11/14. Results: Demographic characteristics reveal that highest percentage (84 %) of them belongs to the Hindu religion and had one child below the 6 months of the age. Comparisons of the knowledge score with demography highest mean and SD in relation to family income Rs 4001 - 6000 shows that (14.7 ± 1.16). The Overall Mean knowledge score was (11.5 ± 3.26)and (50 %) revealing average knowledge. However there was significant association between knowledge score and education & type of family (P = 0.0151 & P = 0.0091) revealing that maximum demographic variables do not affected the level of knowledge. Conclusion: The overall knowledge is average. However lowest percentage in the areas of “principles of feeding and storage” and “age of introducing on weaning” were attention seeking, implying the necessity to improve the knowledge in regard to prevent malnutrition. JCMS Nepal. 2015;11(1): 12-16